2021
DOI: 10.3390/ma14123341
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Reactive Powder Concrete Containing Expanded Perlite

Abstract: This paper presents the test results of the lightweight concrete properties obtained by adding expanded perlite (EP) to an RPC mix in quantities from 30% to 60% by volume of the concrete mix. It has been shown that in these cases it is possible to obtain concrete containing 30% by volume with density of approximately 1900 kg/m3 and the compressive strength > 70 MPa, with a very low water absorption value (3.3%), equal to the water absorption value of RPC without lightweight aggregate (3.3%). However, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The effect of perlite on strength can be explained by the formation of close particle packing and the creation of strong monolithic films. Furthermore, the pozzolanic reaction between perlite and calcium hydroxide can take place, which could lead to the increasing of durability [ 64 , 65 ]. The perlite sand increases mixed thixotropy as well; this can be seen from Table 6 , where b 2 = 84.3.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of perlite on strength can be explained by the formation of close particle packing and the creation of strong monolithic films. Furthermore, the pozzolanic reaction between perlite and calcium hydroxide can take place, which could lead to the increasing of durability [ 64 , 65 ]. The perlite sand increases mixed thixotropy as well; this can be seen from Table 6 , where b 2 = 84.3.…”
Section: Resultsmentioning
confidence: 99%
“…The strength of the cement-aggregate composite is a function of the strength of the cement matrix, the strength of the aggregate and the bond between these phases [82]. In case of heating in the studied range, the sand and perlite generally remain unchanged [26,83]. Changes are present in the cement matrix.…”
Section: Mechanical Properties Of Mortarsmentioning
confidence: 99%
“…It also possesses one of the lowest densities among other lightweight materials suitable for aggregate use [22], and it has the potential to effect internal self-curing in cement composites due to its water retention abilities [23,24]. It is manufactured by grinding and firing natural rock at 800-1200 • C. Under these conditions, the rock softens and the water in it turns into steam and causes expansion [25,26]. Perlite rock is an amorphous material which consists mainly of silicon dioxide [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, fillers for lightweight concrete mainly include expanded perlite [ 14 , 15 ], foam particles (such as polystyrene foam balls [ 16 , 17 ], ceramic balls [ 18 , 19 ], and so on), and expanded clay [ 20 , 21 ]. Stefania Grzeszczyk et al [ 22 ] added expanded perlite to concrete to obtain lightweight concrete. Test results showed that the density of lightweight concrete was 1900 kg/m 3 , and the compressive strength was >70 MPa when filled with 30 vol% expanded perlites.…”
Section: Introductionmentioning
confidence: 99%